Prospective study of infantile haemangiomas: incidence, clinical characteristics and association with placental anomalies3. (April 2014) - Munden, A.; Butschek, R.; Tom, W.L.; Marshall, J. S.; Poeltler, D. M.; Krohne, S.E.; Alió, A.B.; Ritter, M.; Friedlander, D.F.; Catanzarite, V.; Mendoza, A.; Smith, L.; et al.
Summary Background The aetiology and exact incidence of infantile haemangiomas (IHs) are unknown. Prior studies have noted immunohistochemical and biological characteristics shared by IHs and placental tissue. Objectives We investigated the possible association between placental anomalies and the development of IHs, as well as the demographic characteristics and other risk factors for IHs. Patients and methods Pregnant women (n = 578) were prospectively enrolled and their offspring followed for 9 months. Placental evaluations were performed and demographic data collected on all mother–infant pairs. Results We evaluated 594 infants: 34 haemangiomas [either IH or congenital (CH)] were identified in 29 infants, yielding an incidence of 4·5% for IH (27 infants) and 0·3% for CH (two infants). Placental anomalies were noted in almost 35% of haemangioma‐related pregnancies, approximately twice the incidence noted in pregnancies with unaffected infants (P = 0·025). Other risk factors for IH included prematurity (P = 0·016) and low birth weight (P = 0·028). All IHs were present by 3 months of age, and cessation of growth had occurred in all by 9 months of age. Most occurred on the trunk. Of note, 20% of identified IHs were abortive or telangiectatic in nature, small focal lesions that did not proliferate beyond 3 months of age. Only one IH required intervention. Conclusions This is the first prospective American study to document the incidence of IHs in infants followed from birth to early infancy. The association with placental anomalies was statistically significant. The overall incidence mirrors prior estimates, but the need for treatment was lower than previously reported.